Pork Quality Attributes and Eating Characteristics Among Different Premium and Commodity Pork Loin Programs - Brittany Olson; Emily A Rice; Erin Beyer; Jessie Vipham; John Gonzalez; Lauren L. Prill; Lindsey N. Drey; Michael Chao; Morgan Zumbaugh; Travis O'Quinn (Meat and Muscle Biology, 2023)
Pork branding is a common tool used to differentiate products based on quality to assist consumers in making purchasing decisions. Most pork processers have premium pork programs with different parameters related to color, mar-bling, and other quality factors, though many differences in specific criteria exist among programs. The objective of this study was to assess differences in pork quality and the associated eating experience of different premium and commodity pork loin programs available in the retail market. Loins (n=30/brand) from 7 branded (PRE A, B, C, D, and E) and commodity (COM A and B) programs were acquired and fabricated at 14–15 d post-box date into 2.54-cm chops for visual color, marbling, pH, intramuscular fat, drip loss, purge loss, shear force, and trained sensory panels. Overall, few differences were found among products for most of the quality traits evaluated. One commodity brand, COM B, had higher (P<0.05) loin L* values and chop L* values and had lower chop a* values, visual color scores, pH, and drip loss than other treatments, but it did not differ (P>0.05) in initial juiciness, sustained juiciness, or any tenderness measurement. The only quality measurement that was associated with changes in eating experience was shear force value, with the PRE C product having the highest (P<0.05) Warner-Brazler shear force and slice shear force values and the associated lowest (P<0.05) myofibrillar tenderness and overall tenderness ratings in the sensory panels. There were no differences (P>0.05) among any treatment for initial juiciness, sustained juiciness, and pork flavor intensity. The results from this study indicate that the range of pork quality differences sold domestically among the evaluated premium and commodity programs is minimal and does not result in associated differences in eating experience.